Women Entrepreneurship Development through Cooperatives - Ojha, Bhoj Raj (Management Dynamics, 2018)
Introduction Entrepreneurs are individuals or group of individuals who invest capital, organize and direct business and industrial units. An entrepreneur assembles, coordinates and directs various factors of production namely land, labor, capital and other materials. "An entrepreneur initiates ventures, employs workers, organizes production, develops markets and influences the development of managerial thoughts" (Shrestha, 1982:11). As stated by Higgins "Entrepreneurship is meant the function of seeing investment and production opportunities, organizing an enterprise to undertake a new production process, raising capital, hiring labor, arranging for the supply of raw materials, finding a site and combining these factors of production into a going concern, introducing new techniques and selecting top managers for day to day operation" (Higgins, 1966:88). The elements common to all of them are the desire for breaking away from traditional ways of doing things, face the organizational and technical problems in decision-making process and measure up to the risks which are implicit in the process (Joshi, 1977: 40). Entrepreneurs can be divided into three broad categories i.e., Private Entrepreneur, Government Entrepreneur and Institutional Entrepreneur (K.C., 1989: 18–19).